Are Borrmann’s Types of Advanced Gastric Cancer Distinct Clinicopathological and Molecular Entities? A Western Study - Díaz del Arco, Cristina (Cancers (Basel), 2021)
SIMPLE SUMMARY: Borrmann classification is widely used for advanced gastric cancer (GC). Most studies on the clinicopathological impact of this classification have been performed in Asian countries, and almost all authors analyzed only type IV tumors. We assessed the clinicopathological, molecular features and the prognostic value of Borrmann types in all patients with advanced GC resected in a Western institution (n = 260). We observed a significant relationship between Borrmann types and several clinicopathological and molecular features, including age at diagnosis, systemic symptoms, tumor size, Laurén subtype, presence of signet-ring cells, infiltrative pattern, high grade, necrosis, size of the largest lymph node metastasis, HERCEPTEST positivity, microsatellite instability and molecular subtypes. No association was found between Borrmann classification and prognosis. According to our results, Borrmann types may represent distinct clinicopathological and biological entities. Further studies should be performed to confirm the role of Borrmann classification in the stratification of patients with advanced GC. ABSTRACT: Most studies on the clinicopathological impact of Borrmann classification for gastric cancer (GC) have been performed in Asian patients with type IV tumors, and immunohistochemical features of Borrmann types have scarcely been analyzed. We assessed the clinicopathological, molecular features and prognostic value of Borrmann types in all patients with advanced GC resected in a Western institution (n = 260). We observed a significant relationship between Borrmann types and age, systemic symptoms, tumor size, Laurén subtype, presence of signet-ring cells, infiltrative growth, high grade, tumor necrosis, HERCEPTEST positivity, microsatellite instability (MSI) and molecular subtypes. Polypoid GC showed systemic symptoms, intestinal-type histology, low grade, expansive growth and HERCEPTEST positivity. Fungating GC occurred in symptomatic older patients. It presented intestinal-type histology, infiltrative growth and necrosis. Ulcerated GC showed smaller size, intestinal-type histology, high grade and infiltrative growth. Most polypoid and ulcerated tumors were stable-p53-not overexpressed or microsatellite unstable. Flat lesions were high-grade diffuse tumors with no MSI, and occurred in younger and less symptomatic patients. No association was found between Borrmann classification and prognosis. According to our results, Borrmann types may represent distinct clinicopathological and biological entities. Further research should be conducted to confirm the role of Borrmann classification in the stratification of patients with advanced GC.